Objetivos do desenvolvimento sustentável, Plano Nacional de Educaç\~ao e professores do ensino básico brasileiro - Milko Matijascic; Carolina Esther Kotovicz Rolon (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
Ensuring career enhancement and good working conditions for schoolteachers are vital to guarantee learning opportunities for all, as recons the Sustainable Development Goals (SDG) and Brazilian's National Education Plan (PNE). The present study analyses indicators related to schoolteachers, including PNE and SDG 4 indicators, as well as those on the insertion in the labor market and the number of hours and schools taught in for the years of 2015 and 2019. The results highlight regional inequalities, and among the private and public schools. Despite the advances registered, efforts need to be redoubled to meet the goals agreed upon.
Keywords: I21; I28; J22; 330; school teachers; enhancement of teacher's careers; school teachers' working conditions; National Education Plan; Sustainable Development Goals